2003
DOI: 10.1126/science.1092985
|View full text |Cite
|
Sign up to set email alerts
|

Kinesin Moves by an Asymmetric Hand-Over-Hand Mechanism

Abstract: Kinesin is a double-headed motor protein that moves along microtubules in 8-nanometer steps. Two broad classes of model have been invoked to explain kinesin movement: hand-over-hand and inchworm. In hand-over-hand models, the heads exchange leading and trailing roles with every step, whereas no such exchange is postulated for inchworm models, where one head always leads. By measuring the stepwise motion of individual enzymes, we find that some kinesin molecules exhibit a marked alternation in the dwell times b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
455
2
4

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 483 publications
(476 citation statements)
references
References 28 publications
15
455
2
4
Order By: Relevance
“…Single molecule experiments using optical tweezers [134][135][136] and fluorescence dye 137,138 suggested that kinesin undergoes structural transitions resulting in an alternative binding of motor head to the microtubule binding sites that are 8-nm apart. The force-ATP-velocity (or force-ATP-randomness) relationship measured through the single molecule assays and kinetic ensemble experiments prompted several groups to decipher the energy landscape of motor dynamics by proposing and solving the phenomenological models that best describe the motility data.…”
Section: Kinesinmentioning
confidence: 99%
“…Single molecule experiments using optical tweezers [134][135][136] and fluorescence dye 137,138 suggested that kinesin undergoes structural transitions resulting in an alternative binding of motor head to the microtubule binding sites that are 8-nm apart. The force-ATP-velocity (or force-ATP-randomness) relationship measured through the single molecule assays and kinetic ensemble experiments prompted several groups to decipher the energy landscape of motor dynamics by proposing and solving the phenomenological models that best describe the motility data.…”
Section: Kinesinmentioning
confidence: 99%
“…Experiments with mutants that uncouple phosphate (P i ) release and motor detachment from the microtubule were used to determine the order of steps K5-K7, in which P i release is rate-limiting [24]. With each cycle, the two motor heads exchange position, progressing in an asymmetric hand-over-hand fashion [25][26][27].…”
Section: A Consensus Mechanochemical Cycle For Dimeric Kinesinmentioning
confidence: 99%
“…For example, the dimeric kinesin-1 transports cargo by taking 8 nm steps in a hand-over-hand fashion along microtubules (2)(3)(4)(5). Microtubules consist of circularly arranged protein chains, socalled protofilaments, assembled of a/b-tubulin dimers (1).…”
Section: Introductionmentioning
confidence: 99%